Produção de mudas de mamoeiro cultivadas em substratos provenientes de resíduos orgânicos - Souza, Francisca Evelice Cardoso de (2020)
The use of organic waste for the production of plant substrates is an important environmental and economic alternative. In this perspective, the objective of this study was to evaluate growth, gas exchange and the accumulation of mineral nutrients in papaya seedlings grown in polyethylene bags and polystyrene trays with substrates from organic waste, with or without the addition of biochar. of the green coconut shell. The work was carried out in a greenhouse at the Federal University of Ceará, located in Fortaleza, Ceará, and was divided into two experiments: production of papaya seedlings in a polyethylene bag and production of papaya seedlings in a polystyrene tray. In both experiments, a completely randomized design was adopted. Experiment 1 consisted of four treatments and five repetitions, with six plants in each repetition, with the treatments formed by four types of substrates, three of which came from the composting of sewage sludge, green coconut shell and carnauba bagana, and a commercial Turfa Fertile. Experiment 2 consisted of eight treatments and four repetitions, with ten plants in each repetition, the treatments being composed of eight types of substrates, these being: composting sewage sludge, green coconut shell, carnauba bagana, substrate commercial Turf Fertil, composting sludge + biochar, composting coconut shell + biorchar, composting bagana + biochar and commercial substrate + biochar. The biorchar was produced from green coconut shell, added at a proportion of 10% to the volume of substrates. In both experiments, biometric variables were evaluated: plant height, stem diameter, number of leaves, leaf area, length of the largest root, dry masses (aerial, roots and total) and Dickson's quality index; physiological variables: photosynthesis, stomatal conductance, transpiration, water use efficiency, instant carboxylation efficiency; and, accumulation of nutrients and heavy metals in plants. For the cultivation of papaya in polyethylene bags the substrates of green coconut shell and carnauba bagana proved to be efficient, while for the production of seedlings in polystyrene trays the sewage sludge, sludge + biochar and bagana + biochar were the most suitable. The commercial substrate produced lower quality seedlings in both containers. The addition of green coconut shell biochar to the substrates was beneficial, promoting an increase in the biometric and nutritional variables of the seedlings.